Applying Constructionist Principles to Online Teacher Professional Development - Ostashewski, Nathaniel; Moisey, S.; Reid, D. (Athabasca University, 2011)
This report explores the first iteration of a teacher professional development courseletgrounded in constructionist theory and activities. This online teacher professional development(oTPD) courselet provided opportunities for teachers to engage in just-in-time, ongoingTPD within a social networking site for educators. The topic of the oTPD was Roboticsand Hands-on Activities in the Classroom. The courselet was designed for teachers who areinterested in integrating constructionist pedagogies into their practice. Key findings of thefirst delivery of the oTPD courselet point to a need for flexible access, sharing of resources,and support for constructionist pedagogical activities as a PD value for participants. Findingsfurther support the potential for an ongoing online community of practice around roboticsin the classroom. The approach taken in this oTPD courselet of study continues toinform a model of oTPD delivery within a social-networking-enabled environment.